Mathematics for Critical Numeracy: A Case Study of a Social Justice Mathematics Course for Preservice Elementary Teachers - (:unkn) unknown (My University, 2010)
In spite of undeniable technological progress in our Western society, injustice continues to plague the twenty-first century. More than ever in human history, our civilization faces many obstacles that require our attention. Although some educators have contended that the primary goal of education should be to ensure social well-being, many still question whether all subject areas are inviting students to think about current world conditions and their transformation. For the most part, little focus has been placed on considering a critical mathematics curriculum that relates both content and delivery to considering transformative possibilities for society. Some mathematics educators have begun to question the role their subject plays in developing social well-being; however, not much research exists on how to formulate courses that develop mathematical as well as social knowledge and beliefs, particularly with preservice teachers. In light of these concerns, through my own teaching, I decided to explore the critical factors involved in the evolution of a social justice mathematics content course for elementary preservice teachers. Further, I sought to understand student perceptions about teaching and learning in such a course. My findings suggest that participating in this study increased enjoyment of learning mathematics for the participants, and it transformed their understandings of mathematics and social issues. However, resistance from a few students was encountered.
Keywords: Mathematics--Study and teaching; Social justice--Study and teaching; Student teachers--Education